Robotic Process Automation (RPA): Framework para cálculo de ROI de implantações - Gustavo Souza da Motta (Universidade do Vale do Rio dos Sinos, 2021)
The current work model has been changed by the Fourth Industrial Revolution, also known as Industry 4.0, and the diffusion of its technologies and tools. Some of the main ones are the internet of things, additive manufacturing and artificial intelligence, transforming the way in which methods are handled in companies. This work focused on one of the technologies that emerged from this 4.0 industry: Robotic Process Automation (RPA). With the term created only in 2012, RPA involves process automation, integration between systems and artificial intelligence, to create a new approach to automating business processes. With an increase in production in the market in recent years, uncertainties about the gain, how to apply it and how to measure it, creation of the various sectors in which automation is seen as a competitive alternative. This technology has great potential for gains in process agility, reducing errors, improving the quality of people's work and serving as an alternative to integration solutions between systems for quick gains. Throughout this work, for a better understanding of the applications and estimates of gains in RPA, a study was carried out through a systematic review of the literature and interviews conducted with professionals in the field. After gathering, the data was organized in a systemic way, checking which variables impact the technology ROI and which are the internal and external characteristics of the environment that affect this result. The results of the work seek to indicate what should be considered and evaluated in order to obtain a better evaluation of the ROI and better results with the application of technology.
Keywords: Robotic process automation; RPA; ROI; Pensamento sistêmico; Robotic process automation; Systems thinking